The Impact of Religiosity and Perceived Risk on Sharia Investment Decisions: The Mediating Effect of Perceived Trust - Kusumawati, Rita; Nadia, Linda Putri; Jaboob, Mohammed (Journal of Islamic Economic and Business Research, 2025)
This study empirically tests the influence of risk perception and religiosity on Sharia investment decisions with a perception of trust as a mediating variable. This quantitative study uses a questionnaire survey method. The questionnaire was distributed online using Google Forms. The research sample was taken using a purposive sampling technique with the criteria of being at least 17 years old, Muslim, and having or currently investing in Sharia stocks on the IDX. While hypothesis testing was carried out using Partial Least Square (PLS). The results show that religiosity can increase perceived trust and sharia investment decisions. Perceived risk only affects Sharia investment decisions and does not affect perceived trust. Indirect results show that perceived trust only partially mediates the relationship between religiosity and Sharia investment decisions and does not mediate perceived risk in Sharia investment decisions. This study contributes to developing the Theory of Planned Behavior regarding the factors influencing Sharia investment decisions. The results of this study can serve as a reference for OJK, BEI, and Sharia investment managers in formulating policies on Sharia investments that promote sustainable growth, safeguard investor interests, and uphold the integrity of the Sharia investment market. The research sample is narrow and conducted quantitatively, so the research results are less broad and in-depth.